Preparation method of EVA (Ethylene Vinyl Acetate) waterproof coating
By preparing EVA waterproof coating with a crosslinking network structure, the problem of poor waterproofing performance of existing EVA adhesive films is solved, and the mechanical properties and waterproofing performance of the coating are improved, which can effectively prevent water and harmful ions from entering the inside of the material.
Patent Information
- Application Number
- CN202510086452.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-01-20
AI Technical Summary
The existing EVA adhesive film has poor waterproof performance and is difficult to effectively prevent water and harmful ions from entering the interior of porous materials such as concrete.
By preparing an EVA waterproof coating, the coating with a crosslinking network structure is formed by using epoxy trisiloxane intermediates, para-hydroxytrisiloxane benzoate, hydroxylated EVA, isocyanate modified montmorillonite and other materials.
The prepared EVA waterproof coating has good mechanical properties and waterproof properties, which can effectively prevent water molecules and harmful ions from entering the material, and absorb and transfer impact forces when impacted, delaying the fracture process.
Smart Images

Figure CN119775825A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coatings, and in particular to a method for preparing an EVA waterproof coating. Background Art
[0002] Water, chloride ions and other harmful ions can enter the concrete and some porous materials through the gaps, affecting the durability of the materials and increasing the cost of material maintenance. Therefore, waterproof coatings need to be applied on the surface of the materials to make the materials waterproof and wear-resistant to increase their service life. Therefore, the research and development of new waterproof coatings is the focus of current researchers.
[0003] EVA is an ethylene-vinyl acetate copolymer material with excellent elasticity, flexibility, insulation, and chemical corrosion resistance. It is widely used in wires and cables, films, adhesives, coatings and other fields. Montmorillonite is a natural silicate mineral with a layer of aluminum oxide octahedron sandwiched between two layers of silicon oxide tetrahedrons and a negatively charged surface. It has good dispersibility, impact resistance and other properties. For example, the patent with application publication number CN113930169B discloses a heat-resistant EVA film and its preparation method. The film prepared by the invention has good tensile strength, tear strength and good moisture and heat resistance, but its waterproofness is poor. Summary of the invention
[0004] The technical problem solved by the invention is: to provide a method for preparing an EVA waterproof coating, and the prepared EVA waterproof coating has good mechanical properties and waterproof properties.
[0005] The technical solution of the present invention is:
[0006] A preparation method of an EVA waterproof coating, the preparation method is as follows:
[0007] (1) placing an epoxy trisiloxane intermediate, terephthalic acid, and benzyl triethylammonium chloride in 1,2-dichloroethane, reacting at 75-90° C. for 2.5-4 hours, cooling to room temperature, filtering under reduced pressure, recrystallizing, and drying to obtain p-hydroxy trisiloxane benzoate;
[0008] (2) Place p-hydroxytrisiloxane benzoate, hydroxylated EVA, isocyanate-modified montmorillonite, stannous octoate and tetrahydrofuran solvent in a flask, stir evenly and add toluene diisocyanate thereto, heat to 60-70°C, react for 2-4 hours, cool to room temperature, add water thereto, remove tetrahydrofuran by vacuum distillation, add a defoamer and a dispersant, stir evenly, and obtain an EVA waterproof coating.
[0009] Furthermore, in the step (1), the mass ratio of the epoxytrisiloxane intermediate to terephthalic acid is 1:0.2-0.3.
[0010] Furthermore, the amount of benzyltriethylammonium chloride used in step (1) is 1-1.5% of the total mass of the epoxytrisiloxane intermediate and terephthalic acid.
[0011] Furthermore, in the step (2), the mass ratio of p-hydroxytrisiloxane benzoate, hydroxylated EVA, isocyanate-modified montmorillonite, stannous octoate, and toluene diisocyanate is 5-30:100:0.5-8:0.02-0.12:3-20.
[0012] Furthermore, the preparation method of hydroxylated EVA in step (2) is as follows:
[0013] (3) EVA is placed in a toluene solution, and an isopropanol solution of potassium hydroxide is added at 50-70° C., and the mixture is stirred for reaction for 5-8 hours, and ethanol precipitation is performed, suction filtration is performed, ethanol washing is performed, and drying is performed to obtain hydroxylated EVA.
[0014] Furthermore, in step (3), the mass ratio of EVA to potassium hydroxide is 100:5-7.
[0015] Furthermore, the preparation method of the isocyanate-modified montmorillonite in step (2) is as follows:
[0016] (4) Under nitrogen protection, activated montmorillonite and toluene diisocyanate are placed in a toluene solvent and stirred for 20-40 minutes, the temperature is raised for reaction, the mixture is cooled to room temperature, filtered, washed, and vacuum dried to obtain isocyanate-modified montmorillonite.
[0017] Furthermore, in the step (4), the mass ratio of activated montmorillonite to toluene diisocyanate is 1:0.2-0.5.
[0018] Furthermore, in step (4), the heating reaction time is 60-100 min and the temperature is 70-90°C.
[0019] The beneficial technical effects of the present invention are:
[0020] Activated montmorillonite reacts with toluene diisocyanate to obtain isocyanate-modified montmorillonite. EVA is hydrolyzed under the catalysis of potassium hydroxide to obtain hydroxylated EVA. The epoxy trisiloxane intermediate reacts with terephthalic acid under the ring-opening esterification of benzyl triethylammonium chloride to obtain p-hydroxy trisiloxane benzoate. P-hydroxy trisiloxane benzoate, hydroxylated EVA, isocyanate-modified montmorillonite, and toluene diisocyanate cross-linking reaction are carried out under the catalysis of stannous octoate, and then a defoamer and a dispersant are added thereto and stirred evenly to obtain an EVA waterproof coating.
[0021] The coating prepared by the present invention has a large cross-linked network structure, high density, low surface tension, and is distributed on the surface of the material. Water molecules and other ions cannot enter the interior of the material, and the coating has a good waterproof effect. Moreover, when impacted, the large network structure can also absorb more impact force, transfer the impact force received by the material, reduce the concentration of stress, delay the fracture process, and improve the mechanical properties of the material. In addition, the siloxane structure can produce a cross-linked structure through hydrolysis and gelation, limit the entry of water molecules, and improve the waterproof performance of the material. The montmorillonite used in the present invention has good mechanical properties, but its surface has active groups such as hydroxyl groups, firstly, it is surface modified to reduce the surface free energy, and then it is used as a reactant to undergo a chemical reaction, and applied to the EVA waterproof coating to improve the mechanical properties of the coating. The EVA waterproof coating prepared by the present invention has good mechanical properties and waterproof performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 It is the preparation route of 4-hydroxytrisiloxane benzoate. DETAILED DESCRIPTION
[0023] In order to make the purpose, technical solutions and advantages of the present application clearer, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0024] Preparation method of epoxy trisiloxane intermediate: 1,1,1,3,5,5,5-heptamethyl trisiloxane and allyl glycidyl ether in a molar ratio of 1:1.05 are placed in an isopropanol solution, and an alcohol solution of chloroplatinic acid is added thereto under a nitrogen atmosphere. The reaction is carried out at 90° C. for 5 hours, and the solvent is evaporated. Low boiling substances are removed in vacuo at 85° C. and 60 kPa for 30 minutes, and the mixture is cooled to room temperature to obtain an epoxy trisiloxane intermediate.
[0025] Preparation method of activated montmorillonite: Under a nitrogen atmosphere, montmorillonite is placed in a flask and activated at 250° C. for 2 hours to obtain activated montmorillonite.
[0026] Example 1
[0027] (1) Under nitrogen protection, 60 g of activated montmorillonite and 15 g of toluene diisocyanate were placed in a toluene solvent and stirred for 30 min, heated to 80° C., reacted for 80 min, cooled to room temperature, filtered, washed, and vacuum dried to obtain isocyanate-modified montmorillonite.
[0028] (2) 80 g of EVA was placed in a toluene solution, and 5 g of potassium hydroxide was added to an isopropanol solution, and the two solutions were stirred to dissolve. The two solutions were mixed, and stirred to react at 60° C. for 7 h, and ethanol precipitation was performed, suction filtration was performed, ethanol washing was performed, and drying was performed to obtain hydroxylated EVA.
[0029] (3) 12 g of epoxy trisiloxane intermediate, 3-terephthalic acid, and 0.2 g of benzyl triethylammonium chloride were placed in 1,2-dichloroethane, reacted at 80° C. for 4 h, cooled to room temperature, filtered under reduced pressure, recrystallized, and dried to obtain p-hydroxy trisiloxane benzoate.
[0030] (4) 10 g of p-hydroxytrisiloxane benzoate, 200 g of hydroxylated EVA, 1 g of isocyanate-modified montmorillonite, 0.1 g of stannous octoate and tetrahydrofuran solvent were placed in a flask, stirred evenly and 20 g of toluene diisocyanate was added thereto, the temperature was raised to 65°C, the reaction was carried out for 4 hours, the temperature was lowered to room temperature, water was added thereto, tetrahydrofuran was removed by vacuum distillation, 1.5 g of defoamer BKY-141 and 0.8 g of titanate dispersant NXH-1242 were added, the mixture was stirred evenly, and an EVA waterproof coating was obtained.
[0031] Example 2
[0032] (1) Under nitrogen protection, 60 g of activated montmorillonite and 20 g of toluene diisocyanate were placed in a toluene solvent and stirred for 30 min, heated to 90° C., reacted for 100 min, cooled to room temperature, filtered, washed, and vacuum dried to obtain isocyanate-modified montmorillonite.
[0033] (2) 80 g of EVA was placed in a toluene solution, and 5.6 g of potassium hydroxide was added to an isopropanol solution, stirred to dissolve, and the two solutions were mixed. The two solutions were stirred and reacted at 50° C. for 7 h, ethanol precipitation was performed, suction filtration was performed, ethanol washing was performed, and drying was performed to obtain hydroxylated EVA.
[0034] (3) 12 g of epoxy trisiloxane intermediate, 3.5 g of terephthalic acid, and 0.23 g of benzyl triethylammonium chloride were placed in 1,2-dichloroethane, reacted at 90° C. for 3 h, cooled to room temperature, filtered under reduced pressure, recrystallized, and dried to obtain p-hydroxy trisiloxane benzoate.
[0035] (4) 26 g of p-hydroxytrisiloxane benzoate, 200 g of hydroxylated EVA, 6 g of isocyanate-modified montmorillonite, 0.24 g of stannous octoate and tetrahydrofuran solvent were placed in a flask, stirred evenly and 25 g of toluene diisocyanate was added thereto, the temperature was raised to 70°C, the reaction was carried out for 3 hours, the temperature was lowered to room temperature, water was added thereto, tetrahydrofuran was removed by vacuum distillation, 1.5 g of defoamer BKY-141 and 0.8 g of titanate dispersant NXH-1242 were added, the mixture was stirred evenly, and an EVA waterproof coating was obtained.
[0036] Example 3
[0037] (1) Under nitrogen protection, 60 g of activated montmorillonite and 20 g of toluene diisocyanate were placed in a toluene solvent and stirred for 20 min, heated to 80° C., reacted for 70 min, cooled to room temperature, filtered, washed, and vacuum dried to obtain isocyanate-modified montmorillonite.
[0038] (2) 80 g of EVA was placed in a toluene solution, and 5 g of potassium hydroxide was added to an isopropanol solution, stirred to dissolve, and the two solutions were mixed. The two solutions were stirred and reacted at 60° C. for 6 h, ethanol precipitation was performed, suction filtration was performed, ethanol washing was performed, and drying was performed to obtain hydroxylated EVA.
[0039] (3) 12 g of epoxy trisiloxane intermediate, 3.5 g of terephthalic acid, and 0.15 g of benzyl triethylammonium chloride were placed in 1,2-dichloroethane, reacted at 80° C. for 3 h, cooled to room temperature, filtered under reduced pressure, recrystallized, and dried to obtain p-hydroxy trisiloxane benzoate.
[0040] (4) 42 g of p-hydroxytrisiloxane benzoate, 200 g of hydroxylated EVA, 11 g of isocyanate-modified montmorillonite, 0.15 g of stannous octoate and tetrahydrofuran solvent were placed in a flask, stirred evenly and 20 g of toluene diisocyanate was added thereto, the temperature was raised to 65 ° C, the reaction was carried out for 4 hours, the temperature was lowered to room temperature, water was added thereto, tetrahydrofuran was removed by vacuum distillation, 1.5 g of defoaming agent BKY-141 and 0.8 g of titanate dispersant NXH-1242 were added, and the mixture was stirred evenly to obtain an EVA waterproof coating.
[0041] Example 4
[0042] (1) Under nitrogen protection, 60 g of activated montmorillonite and 20 g of toluene diisocyanate were placed in a toluene solvent and stirred for 30 min, heated to 80° C., reacted for 80 min, cooled to room temperature, filtered, washed, and vacuum dried to obtain isocyanate-modified montmorillonite.
[0043] (2) 80 g of EVA was placed in a toluene solution, and 5.6 g of potassium hydroxide was added to an isopropanol solution, stirred to dissolve, and the two solutions were mixed. The two solutions were stirred and reacted at 60° C. for 7 h, ethanol precipitation was performed, suction filtration was performed, ethanol washing was performed, and drying was performed to obtain hydroxylated EVA.
[0044] (3) 12 g of epoxy trisiloxane intermediate, 3-terephthalic acid, and 0.2 g of benzyl triethylammonium chloride were placed in 1,2-dichloroethane, reacted at 80° C. for 3 h, cooled to room temperature, filtered under reduced pressure, recrystallized, and dried to obtain p-hydroxy trisiloxane benzoate.
[0045] (4) 60 g of p-hydroxytrisiloxane benzoate, 200 g of hydroxylated EVA, 16 g of isocyanate-modified montmorillonite, 0.24 g of stannous octoate and tetrahydrofuran solvent were placed in a flask, stirred evenly and 30 g of toluene diisocyanate was added thereto, the temperature was raised to 65°C, the reaction was carried out for 3 h, the temperature was lowered to room temperature, water was added thereto, tetrahydrofuran was removed by vacuum distillation, 1.5 g of defoamer BKY-141 and 0.8 g of titanate dispersant NXH-1242 were added, the mixture was stirred evenly, and an EVA waterproof coating was obtained.
[0046] Comparative Example 1
[0047] (1) 80 g of EVA was placed in a toluene solution, and 5 g of potassium hydroxide was added to an isopropanol solution, stirred to dissolve, and the two solutions were mixed, stirred and reacted at 60° C. for 7 h, ethanol precipitated, filtered, washed with ethanol, and dried to obtain hydroxylated EVA.
[0048] (2) 12 g of epoxy trisiloxane intermediate, 3-terephthalic acid, and 0.2 g of benzyl triethylammonium chloride were placed in 1,2-dichloroethane, reacted at 80° C. for 4 h, cooled to room temperature, filtered under reduced pressure, recrystallized, and dried to obtain p-hydroxy trisiloxane benzoate.
[0049] (3) 10 g of p-hydroxytrisiloxane benzoate, 200 g of hydroxylated EVA, 0.1 g of stannous octoate and tetrahydrofuran solvent were placed in a flask, stirred evenly and 20 g of toluene diisocyanate was added thereto, the temperature was raised to 65 ° C, the reaction was carried out for 4 hours, the temperature was lowered to room temperature, water was added thereto, tetrahydrofuran was removed by vacuum distillation, 1.5 g of defoamer BKY-141 and 0.8 g of titanate dispersant NXH-1242 were added, and the mixture was stirred evenly to obtain an EVA waterproof coating.
[0050] Comparative Example 2
[0051] (1) Under nitrogen protection, 60 g of activated montmorillonite and 15 g of toluene diisocyanate were placed in a toluene solvent and stirred for 30 min, heated to 80° C., reacted for 80 min, cooled to room temperature, filtered, washed, and vacuum dried to obtain isocyanate-modified montmorillonite.
[0052] (2) 200 g of hydroxylated EVA, 1 g of isocyanate-modified montmorillonite, 0.1 g of stannous octoate and tetrahydrofuran solvent were placed in a flask, stirred evenly and 20 g of toluene diisocyanate was added thereto, the temperature was raised to 65 ° C, the reaction was carried out for 4 hours, the temperature was lowered to room temperature, water was added thereto, tetrahydrofuran was removed by vacuum distillation, 1.5 g of defoaming agent BKY-141 and 0.8 g of titanate dispersant NXH-1242 were added, and the mixture was stirred evenly to obtain an EVA waterproof coating.
[0053] The prepared waterproof coating was applied on a polytetrafluoroethylene plate to form a 1.5 mm thick film, which was cured for one week under standard test conditions and the performance was tested. The standard test conditions were a temperature of 23±2°C and a relative humidity of (50±10)%.
[0054] The mechanical properties of the samples were tested using an electronic tensile testing machine.
[0055] Tensile strength / MPa Elongation at break / % Example 1 10.31 117.0 Example 2 15.96 146.3 Example 3 18.60 163.4 Example 4 16.12 156.9 Comparative Example 1 9.21 104.3 Comparative Example 2 10.13 116.4
[0056] The tensile strength and elongation at break of Example 3 are relatively large, which are 11.60 MPa and 124.1% respectively. The tensile strength and elongation at break of Comparative Example 1 are the smallest. This is because montmorillonite is added to Examples 1-5 and Comparative Example 2, and montmorillonite has good mechanical properties. In addition, since Examples 1-5 and Comparative Example 1-2 both contain relatively excellent cross-linked network structures, they can transfer the impact force exerted on the material when impacted, thereby enhancing the mechanical properties of the coating.
[0057] The water resistance of paint coatings is tested with reference to GB / T 16777-2008 "Test methods for building waterproof coatings" and GB / T1733-1993 "Determination of water resistance of paint films".
[0058] Waterproofness (0.3MPa, 120min) Water resistance Example 1 impermeable No peeling, no blistering, qualified Example 2 impermeable No peeling, no blistering, qualified Example 3 impermeable No peeling, no blistering, qualified Example 4 impermeable No peeling, no blistering, qualified Comparative Example 1 impermeable Peeling, no blistering, unqualified Comparative Example 2 permeable Peeling, blistering, unqualified
[0059] Examples 1-5 and Comparative Example 1 are all impermeable, but Comparative Example 2 is permeable. The water resistance of Examples 1-5 is not peeling or blistering, and is qualified. This is because Examples 1-5 and Comparative Example 1 contain siloxane structures, which can produce cross-linked structures through hydrolysis and gelation, restrict the entry of water molecules, and improve the waterproof performance of the material. In addition, the structure prepared by the present invention has a lower surface energy and also has good hydrophobic and waterproof performance. Therefore, the waterproof effect of Comparative Example 2 is the worst.
[0060] The present application is described in detail above in conjunction with specific implementation methods and exemplary examples, but these descriptions cannot be understood as limiting the present application. Those skilled in the art understand that, without departing from the spirit and scope of the present application, a variety of equivalent replacements, modifications or improvements can be made to the technical solution of the present application and its implementation methods, all of which fall within the scope of the present application. The scope of protection of the present application shall be subject to the attached claims.
Claims
1. A method for preparing an EVA waterproof coating, characterized in that: The preparation method is as follows: (1) placing an epoxy trisiloxane intermediate, terephthalic acid, and benzyl triethylammonium chloride in 1,2-dichloroethane, reacting at 75-90° C. for 2.5-4 hours, cooling to room temperature, filtering under reduced pressure, recrystallizing, and drying to obtain p-hydroxy trisiloxane benzoate; (2) Place p-hydroxytrisiloxane benzoate, hydroxylated EVA, isocyanate-modified montmorillonite, stannous octoate and tetrahydrofuran solvent in a flask, stir evenly and add toluene diisocyanate thereto, heat to 60-70°C, react for 2-4 hours, cool to room temperature, add water thereto, remove tetrahydrofuran by vacuum distillation, add a defoamer and a dispersant, stir evenly, and obtain an EVA waterproof coating.
2. The preparation method of the EVA waterproof coating according to claim 1, characterized in that: In the step (1), the mass ratio of the epoxytrisiloxane intermediate to terephthalic acid is 1:0.2-0.
3.
3. The preparation method of the EVA waterproof coating according to claim 1, characterized in that: The amount of benzyltriethylammonium chloride used in step (1) is 1-1.5% of the total mass of the epoxytrisiloxane intermediate and terephthalic acid.
4. The preparation method of the EVA waterproof coating according to claim 1, characterized in that: In the step (2), the mass ratio of p-hydroxytrisiloxane benzoate, hydroxylated EVA, isocyanate-modified montmorillonite, stannous octoate and toluene diisocyanate is 5-30:100:0.5-8:0.02-0.12:3-20.
5. The preparation method of the EVA waterproof coating according to claim 1, characterized in that: The preparation method of hydroxylated EVA in step (2) is as follows: (3) placing EVA in a toluene solution, adding an isopropanol solution of potassium hydroxide at 50-70° C., stirring for reaction for 5-8 hours, ethanol precipitation, suction filtration, ethanol washing, and drying to obtain hydroxylated EVA.
6. The preparation method of the EVA waterproof coating according to claim 5, characterized in that: In the step (3), the mass ratio of EVA to potassium hydroxide is 100:5-7.
7. The preparation method of the EVA waterproof coating according to claim 1, characterized in that: The preparation method of the isocyanate-modified montmorillonite in step (2) is as follows: (4) Under nitrogen protection, activated montmorillonite and toluene diisocyanate are placed in a toluene solvent and stirred for 20-40 minutes, the temperature is raised for reaction, the mixture is cooled to room temperature, filtered, washed, and vacuum dried to obtain isocyanate-modified montmorillonite.
8. The preparation method of the EVA waterproof coating according to claim 7, characterized in that: In the step (4), the mass ratio of activated montmorillonite to toluene diisocyanate is 1:0.2-0.
5.
9. The method for preparing the EVA waterproof coating according to claim 7, characterized in that: The heating reaction time in step (4) is 60-100 minutes, and the temperature is 70-90°C.
Citation Information
Patent Citations
A heat-resistant EVA film and its preparation method
CN113930169B
Preparation method of printing adhesive for digital printing
CN110106729A